2021
DOI: 10.1111/ppa.13355
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive diversity assessment of walnut‐associated xanthomonads reveal the occurrence of distinct Xanthomonas arboricola lineages and of a new species (Xanthomonas euroxanthea) within the same tree

Abstract: Xanthomonas arboricola pv. juglandis (Xaj) is the aetiological agent of walnut diseases causing economic losses on walnut production worldwide. This phytopathogen is spread around the world where walnuts are produced and has a considerable genetic diversity. Using a comprehensive sampling methodology, focusing on factors that could influence the diversity of walnut‐colonizing Xaj in Portugal, this work provides new insights on xanthomonad populations on walnut. Genetic diversity was assessed by multilocus sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
(163 reference statements)
0
9
0
Order By: Relevance
“…It is important to investigate the distribution and role played by X. euroxanthea and the closely related X. arboricola within the plant hosts that they frequently co-colonize [12]. Therefore, it is essential to develop a reliable and efficient method for the accurate detection and identification of X. euroxanthea strains and its differentiation from X. arboricola [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is important to investigate the distribution and role played by X. euroxanthea and the closely related X. arboricola within the plant hosts that they frequently co-colonize [12]. Therefore, it is essential to develop a reliable and efficient method for the accurate detection and identification of X. euroxanthea strains and its differentiation from X. arboricola [12].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, multiplex-PCR and dot-blot hybridization assays showed that three X. arboricola pv. juglandis specific DNA markers (XAJ1, XAJ6 and XAJ8) were absent from X. euroxanthea strains CPBF 367, CPBF 424 T and CPBF 426, which formed a distinct MLSA cluster [12,14].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…These nonpathogenic strains, also sometimes referred to as look-alikes of Xanthomonas pathogens, have been isolated from a wide diversity of organs and plant species, such as seeds, buds, leaves from legumes, cereals, and fruit trees [23][24][25][26][27]. Non-pathogenic strains are interspersed with pathogenic ones at an infraspecific level, especially within the X. arboricola and X. euroxanthea species [11,[28][29][30], which implies that highly specific detection tools are required to avoid confusion that could have harmful socio-economic consequences. The coexistence of pathogenic and non-pathogenic Xanthomonas strains in the same host plant largely increased the estimated diversity in the genus [6,19,24,[30][31][32], with events such as recombination and horizontal gene transfer contributing to the pathogen diversification across the different pathosystems [28,[33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%